#### Answer

$-(-x))=-5$

#### Work Step by Step

If $x=-5$, by substituting in the given expression we get:
$-(-x)=-(-(-5))=-(+5)=-5$

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$-(-x))=-5$

If $x=-5$, by substituting in the given expression we get:
$-(-x)=-(-(-5))=-(+5)=-5$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.